Detection of micrometastasis in axillary lymph nodes of breast carcinoma patients and its association with clinical outcome - Indu Ramachandran Nair; Anand John Mathew; Vijaykumar Dehannaparambil Kottarathil (Wolters Kluwer Medknow Publications, 2018)
Context: There is heterogeneity in the clinical behavior of breast carcinoma patients with node negativity. Studies have analyzed different factors influencing the outcome in such patients. It is suggested that the presence of nodal micrometastasis can act as a tool in predicting the aggressiveness of these tumors. Aims: The aim of this study is to assess the yield of micrometastasis/isolated tumor cell (ITC) by ultrastaging the morphologically negative axillary nodes and staining them with immunohistochemistry for epithelial membrane antigen. The association of such metastasis with the clinical outcome is determined. Settings and Design: This was a retrospective analytical study. One hundred cases of node-negative breast carcinoma patients who underwent surgery along with axillary lymph node dissection were selected. Materials and Methods: The largest node from the axillary dissection was selected and subjected to ultrastaging and immunohistochemical staining (as sentinel node dissection was not a routine practice at that time), to look for occult metastasis in the form of micrometastasis or ITCs. Statistical Analysis: Occurrence of events in the form of recurrence or death was noted. Association of the parameters was analyzed using Fisher's exact test. Results: Among the 100 cases, 79 patients were followed up for a minimum period of 5 years. Two cases had micromets in one node each. These two patients were among the eight, who developed events subsequently (25%). Hence, a statistically significant association was found between the presence of micromets with events. Conclusions: There is a statistically significant association between the presence of micromets and disease recurrence. Hence, we suggest that ultrastaging of the negative axillary node (now sentinel node, as it is being routinely done) might prove effective in predicting the events/prognosis in clinically and morphologically node-negative breast carcinoma patients